(untitled) (Ahkam: Jurnal Hukum Islam, 2022)
ABSTRACT This paper focuses on discussing how the implementation of Neo Visibility Hilal MABIMS in Indonesia when it is in a system that applies in a country that also has its own method of determining the beginning of the month of Qamariyah. This research data is sourced from data on how the implementation of Neo Visibility Hilal MABIMS in Indonesia is also enriched with several previous research results related to this reality. The results show that since 1972, the Ministry of Religious Affairs has established the Hisab Rukyat Agency (BHR), which is in charge of conducting hisab and rukyatul hilal to determine the beginning of the month of Qamariyah, especially for religious days. The beginning of the month is marked by the appearance of the hilal above the horizon, but this limit on the height of the hilal gives birth to differences of opinion. The Indonesian government sets the standards and criteria for setting the beginning of the month with imkanur rukyat. The Imkanur rukyat is the minimum limit of visible hilal. This is because the position of the hilal varies depending on the matlak Keywords: MABIMS, Neo Visibility Hilal, Imkanur Rukyat, Beginning of the Month of Qomariyah